2003
DOI: 10.1074/jbc.m212449200
|View full text |Cite
|
Sign up to set email alerts
|

The First Crystal Structure of Archaeal Aldolase

Abstract: A gene encoding a 2-deoxy-D-ribose-5-phosphate aldolase (DERA) homolog was identified in the hyperthermophilic Archaea Aeropyrum pernix. The gene was overexpressed in Escherichia coli, and the produced enzyme was purified and characterized. The enzyme is an extremely thermostable DERA; its activity was not lost after incubation at 100°C for 10 min. The enzyme has a molecular mass of ϳ93 kDa and consists of four subunits with an identical molecular mass of 24 kDa. This is the first report of the presence of tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 39 publications
1
18
1
1
Order By: Relevance
“…Interestingly, the dimer interface of Tg DPA forms around the flipped out N-terminal helix (Fig. 2B), similar to the dimerization interface predicted for Py DERA [46], but significantly different than the dimer and tetramer-forming interfaces observed for other dR5P aldolases [44, 47, 48]. Additionally, no salt bridges and only one hydrogen bond were present at the interface consistent with a largely hydrophobic-based assembly.…”
Section: Resultssupporting
confidence: 60%
“…Interestingly, the dimer interface of Tg DPA forms around the flipped out N-terminal helix (Fig. 2B), similar to the dimerization interface predicted for Py DERA [46], but significantly different than the dimer and tetramer-forming interfaces observed for other dR5P aldolases [44, 47, 48]. Additionally, no salt bridges and only one hydrogen bond were present at the interface consistent with a largely hydrophobic-based assembly.…”
Section: Resultssupporting
confidence: 60%
“…An enlargement of the oligomatic interface is also shown to be important for the thermostability, for instance, in 2-deoxy-D-ribose-5-phosphate aldolase. 19 However, we found that the dimer contact area of DHQS is independent of the living temperature. From these results, the dimeric state of DHQS might not contribute to the thermostability, probably because the wellconserved dimeric structure itself is relevant to the catalytic function of this enzyme.…”
contrasting
confidence: 38%
“…EA01524.86509.1137 c Maximal activity at 200 mM(Kim et al 2009)  Paenibacillus sp . EA00124.565014562 c n.s.(Kim et al 2010)  Rhodococcus erythropolis 22.9725 e 4.8417 c Half-life = 64.4 min300 mM 25 °C(Kullartz and Pietruszka 2012)  Haemophilus influenza 23.67.5400.1470.42 b Maximal activity at 300 mM(Woo et al 2014)  Staphylococcus epidermidis 29.2n.s.67.1 c 11.3% retention of activity2 h 300 mM 25 °C(Fei et al 2015)  Lactobacillus brevis ECU8302n.s.6403.34102 b Half-life = 37.3 min300 mM 25 °C(Jiao et al 2015)Extremophiles (hyperthermophilic unless specified)  Aeropyrum pernix 24.56.5n.s.0.057**4.5 c **n.s.(Sakuraba et al 2003)  Thermococcus kodakaraensis 24.54950.81***285 b ***n.s.(Rashid et al 2004)  Pyrobaculum aerophilum 24.56n.s.0.0660.25 c 53% retention of activity20 h 300 mM 25 °C(Sakuraba et al 2007)  Thermotoga maritima 27.86.5n.s.0.021 c 46% retention of activity20 h 300 mM 25 °C(Sakuraba et al 2007)  Hyperthermus butylicus 26.45.5800.150.5 c 75% retention of activity8 h 300 mM 25 °C(Wang et al 2010)  Aciduliprofundum boonei 26.67800.12n.s.70% retention of activity4 h 250 mM 25 °C(Yin et al 201...…”
Section: Substrate Specificitymentioning
confidence: 99%